Badranaya: A Board Game to Enhance Prospective Multicultural Counselors’ Impartial Character - Setyaputri, Nora Yuniar; Krisphianti, Yuanita Dwi; Nawantara, Rosalia Dewi (Jurnal Kajian Bimbingan dan Konseling, 2024)
The discriminative behavior upon individual personalities that multicultural counselors have frequently operated causes low neutrality in encountering an issue and individual labeling. That behavior indicates the counselors lack impartial character. Thus, this study aims to develop a guidance and counseling media of Badranaya (multicultural counseling board game) that promote unbiased character, referring to Semar’s great characters. It used modified Borg and Gall development procedures, while its data were obtained through valid and reliable experts assessment questionnaire and impartial character scale. The numerical data analysis results from guidance and counseling experts, as well as educational media development experts, signify that this media is highly feasible to be used. Meanwhile, the qualitative data from experts in the related fields also confirms the media’s feasibility to be adopted as a new educational media breaktrough, primarily in prospective counselors’ education. Additionally, the paired sample test results also show an increase in the multicultural counselors’ impartial character after they play Badranaya.